Economically important underutilized fruits suitable for arid eco-system: A review (Indian Journal of Arid Horticulture, 2023)
Climatic conditions of the western Rajasthan and some part of Gujarat are characterized by low and erratic rainfall, high thermal oscillation and harsh climatic conditions. Therefore, the land is barren and can be utilized for production of arid fruits which are yet underutilized. Some Fruits like Kair (Capparis deciduas L.), Karonda (Carissa carandas L.), Khejri (Prosopis cineraria), Pilu (Salvadora oleoides), Tamarind (Tamarindus indica), Woodapple (Feronia limonia L.) Swingle), Cactus pear (Opuntia ficus-indica), Dragon fruit (Hylocereus Spp.), Nagphani (Opuntia elatior Mill.), Dansara (Rhus mysorenis Hene ex Wight & Arn.) etc are considered as the underutilized fruits. All these fruit crops are grown naturally and being utilized by local people since long owing to their nutritional values as well as capability to resist the harsh climatic conditions. The fruits crops which are still underexploited and have potential to grow in harsh conditions have been reviewed here. The value addition, post harvest management and future prospects of these crops have also been discussed.
Keywords: Arid eco-system; me dicinal value; underutilized fruit; Minor arid fruits